The point of no return : American democracy at the crossroads - Edsall, Thomas Byrne (Princeton, USA : Princeton University Press, 2023)
"How Donald Trump laid waste to American politics, culture, and social order. After Donald Trump's rise to power, after the 2020 presidential election, after January 6, is American politics past the point of no return? New York Times columnist and political reporter Thomas Byrne Edsall fears that the country may be headed over a cliff, arguing that the election of Donald Trump was the most serious threat to the American political system since the Civil War. In this compelling and illuminating book, Edsall documents how the Trump years ravaged the nation's politics, culture, and social order. He explains the demographic shifts that helped make Trump's election possible, and describes the racial and ethnic conflict, culture wars, rural/urban divide, diverging economies of red and blue states, and the transformation of both the Republican and Democratic parties that have left our politics in a state of permanent hostility. The Point of No Return brings together a series of Edsall's columns, bookended by a new introduction and conclusion, which show how we got to this dangerous point. These dispatches from our new political landscape chronicle the emergence of what Edsall calls "the not-so-silent white majority" and show how Trump deployed fears about race and immigration to appeal to voters. Edsall examines Trump's construction of an alternate reality, discusses why we don't always vote according to our own self-interest, and explores the Democrats' calibrated response. Considering the 2020 election and its violent aftermath, Edsall looks at the Capitol insurrection and warns that American democracy is under siege. The forces behind Trump's election, and the "stop the steal" true believers, have pushed the nation to the brink"--
The not-so-silent White majority, Nov. 16, 2016 -- The great Trump reshuffle, May 4, 2016 -- Why Trump now? March 1, 2016 -- How the other fifth lives, April 27, 2016 -- Whose neighborhood is it? Sept. 19, 2015 -- Purity, disgust, and Donald Trump, Jan. 6, 2016 -- Donald Trump's alt-reality, Dec. 15, 2016 -- Reaching out to the voters the Left left behind, April 13, 2017 -- Democracy, disrupted, March 2, 2017 -- Democracy can plant the seeds of its own destruction, Oct. 19, 2017 -- President Trump is the enemy of their enemies, May 4, 2017 -- The end of the Left and the Right as we know them, June 22, 2017 -- Trump says jump. His supporters ask, how high? Sept. 14, 2017 -- The increasing significance of the decline of men, March 16, 2017 -- Robots can't vote, but they helped elect Trump, Jan 11, 2018 -- Trump's tool kit does not include the Constitution, Feb. 8, 2018 -- Trump against the liberal tide, May 31, 2018 -- The class struggle according to Donald Trump, June 7, 2018 -- How much can Democrats count on suburban liberals? June 14, 2018 -- Why don't we always vote in our own self-interest? July 19, 2018 -- The Democrats' left turn is not an illusion, Oct. 18, 2018 -- In our "winner-take-most" economy, the wealth is not spreading, July 26, 2018 -- The deepening "racialization" of American politics, Feb. 27, 2019 -- No one should take Black voters for granted, Sept. 11, 2019 -- Red and blue voters live in different economies, Sept. 25, 2019 -- How can Democrats keep themselves from overreaching? Oct. 9, 2019 -- Is politics a war of ideas or of us against them? Nov. 6, 2019 -- Trump has his sights set on Black voters, March 4, 2020 -- How far might Trump go? Oct. 28, 2020 -- What is Trump playing at? Nov. 11, 2020 -- "The far Left is the Republicans' finest asset" Nov. 18, 2020 -- America, we have a problem, Dec. 16, 2020 -- "The Capitol insurrection was as Christian nationalist as it gets" Jan. 28, 2021 -- White riot, Jan 13, 2021 -- Democracy is weakening right in front of us, Feb. 17, 2021 -- Why Trump still has millions of Americans in his grip, May 5, 2021 -- Is wokeness "kryptonite for Democrats"? May 26, 2021 -- Is education no longer the "great equalizer"? June 23, 2021 -- Trump's cult of animosity shows no sign of letting up, July 7, 2021 -- How strong is America's multiracial democracy? Sept. 1, 2021 -- "It's become increasingly hard for them to feel good about themselves" Sept. 22, 2021 -- Democrats can't just give the people what they want, Oct. 13, 2021 -- The moral chasm that has opened up between left and right is widening, Oct. 27, 2021 -- America has split, and it's now in "very dangerous territory" Jan. 26, 2022.
Includes bibliographical references and indexes.
Keywords: Trump, Donald, -- 1946-; United States. -- Congress -- Elections, 2020.; United States. -- Congress; 2000-2099; Presidents -- United States -- Election -- 2020.; Capitol Riot, Washington, D.C., 2021.; Democracy -- United States -- History -- 21st century; Politics and culture -- United States; Democracy; Elections; Politics and government; United States -- Politics and government -- 2017-2021.; United States; Washington (D.C.); History